The effect of Aloe vera leaf extract on the blood of white mice with induced hyperthyroidism (Journal of Hama University, 2026)
This study aimed to investigate the therapeutic potential of Aloe vera leaf extract in modulating serum levels of FT4, FT3, and TSH in white adult mice with experimentally induced hyperthyroidism.This study included 30 adult female white mice of the Balb/c strain were randomly allocated into three experimental groups, with 10 mice in each group.The first group (physiological control) received a 0.9% NaCl solution throughout the study period, while the second group (pathological control) was administered levothyroxine at a dose of 0.5 mg/kg for 10 days to induce a hyperthyroid state whereas the third group (treatment group) received Aloe vera ethanolic extract at a dose of 500 mg/kg for 30 days following the induction of hyperthyroidism. At the end of the treatment period, blood samples were collected for biochemical evaluation of thyroid hormone levels.The statistical analysis demonstrated that treatment with Aloe vera ethanolic extract significantly ameliorated hyperthyroidism. There was a marked and statistically significant reduction (p
Keywords: Aloe Vera; l; Aloevera leaf exrtract, Hyperthyroidsm, FT4, FT3, TSH, White mice.